2018
DOI: 10.1055/s-0038-1623511
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Indirect Causes of Maternal Morbidity and Mortality in the Process of Obstetric Transition: A Cross-Sectional Multicenter Study

Abstract: A importância das causas indiretas da morbidade e mortalidade maternas no processo de transição obstétrica: um estudo multicêntrico transversal AbstractObjective The aim of this study is to evaluate the burden of indirect causes of maternal morbidity/mortality in Brazil. Methods Secondary analysis of a multicenter cross-sectional study conducted in 27 referral obstetric units within the Brazilian Network for Surveillance of Severe Maternal Morbidity. Results A total of 82,388 women were surveilled: 9,555 wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 23 publications
0
15
1
6
Order By: Relevance
“…Black women had the worst mortality rate (13.6%), which was twice as high as white women (6.7%). The pandemic pattern of COVID‐19 highlights the deficiencies in obstetric care and social inequities in access to health care 2 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Black women had the worst mortality rate (13.6%), which was twice as high as white women (6.7%). The pandemic pattern of COVID‐19 highlights the deficiencies in obstetric care and social inequities in access to health care 2 …”
Section: Discussionmentioning
confidence: 99%
“…At the beginning of the pandemic, a major concern among clinicians was whether pregnant women would represent a group at risk for serious outcomes, as previously seen for acute respiratory distress syndrome (ARDS) caused by the influenza virus. 1,2 New scientific information is continuously being collected. In July 2020, Takemoto et al 3 reported 124 deaths of pregnant or postpartum women with ARDS caused by COVID-19 in 978 Brazilian women.…”
Section: Introductionmentioning
confidence: 99%
“…While data on AO frequency in hospitalized patients (7.6% of patients, 66.7% avoidable AOs) exist, there are none on childbirth care (Mendes et al , 2009). Other studies have investigated the indicators of classic morbidity and mortality or maternal and neonatal near misses, but these conditions are less frequent than obstetric AOs (Cirelli et al , 2018; Silva et al , 2018). Knowing these data might be an essential step in promoting patient safety practices which help improve healthcare quality, and constitute a priority of the World Health Organization (WHO) in attempt to meet the Sustainable Development Goals by 2030 (Kieny et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…3 The highest maternal near miss rates are reported in developing countries 4 and the causes related to maternal near miss in these countries are similar to those of maternal mortality. 2,5 A number of factors that are determinants of mortality are also relevant for morbidity, such as the lack of adequate access to prenatal and childbirth, in addition to the absence of specific technological support, such as an intensive therapy unit or even emergencial blood transfusions. 6 The increase in maternal morbidity rates, especially in low-income countries, demonstrates the inability of the health services to offer quality in maternal care.…”
Section: Introductionmentioning
confidence: 99%